2018
DOI: 10.1155/2018/9817308
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Microbes and Drug Susceptibility in Patients with Diabetic Foot Infections in Southwest China

Abstract: Objective To investigate the microbial distribution and drug susceptibility among diabetic foot ulcers (DFUs) with different Wagner grades and between acute and chronic DFUs. Methods. We enrolled 428 DFU patients who were hospitalized and treated in the Southwest Hospital. We collected deep ulcer secretion for microbial culture and drug susceptibility tests and analyzed the results. We reexamined 67 patients with poor anti-infection efficacy and analyzed microbial species. Results: The 354 positive samples inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
33
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 26 publications
(27 reference statements)
13
33
2
Order By: Relevance
“…In our study, the diabetic patients have superficial wounds of Wagner's grades classification I and II were mostly infected with Gram positive bacteria. Staphylococci and Streptococci species were the predominant pathogens, whereas Gram negative bacteria were more frequently isolated from Wagner's wounds classification grades III and V. These findings are in agreement with various studies concluded that an increasing of Wagner's grades, the proportion of bacterial infections were increased [2,24,35,44,45]. However, the percentage of S. aureus decreased with increased Wagner's grades similar findings reported in other study [24].…”
Section: Bacterial Species Of Dfu Associated With Wagner's Grades Systemsupporting
confidence: 90%
See 3 more Smart Citations
“…In our study, the diabetic patients have superficial wounds of Wagner's grades classification I and II were mostly infected with Gram positive bacteria. Staphylococci and Streptococci species were the predominant pathogens, whereas Gram negative bacteria were more frequently isolated from Wagner's wounds classification grades III and V. These findings are in agreement with various studies concluded that an increasing of Wagner's grades, the proportion of bacterial infections were increased [2,24,35,44,45]. However, the percentage of S. aureus decreased with increased Wagner's grades similar findings reported in other study [24].…”
Section: Bacterial Species Of Dfu Associated With Wagner's Grades Systemsupporting
confidence: 90%
“…In this study, vancomycin showed 83.3% sensitivity of Gram positive bacteria isolated. This similar to other studies 90.1% [55], 95% [36], 98.2% [24], while other study showed low sensitivity of vancomycin 44.5% [44]. However, other studies showed 100% of Gram positive bacteria susceptible to vancomycin [5,27,32,35,50,58].…”
Section: Bacterial Species Of Dfu Associated With Wagner's Grades Systemsupporting
confidence: 87%
See 2 more Smart Citations
“…In India, DFIs commonly are caused by gram-negative bacilli (31). Furthermore, pathogens from India (32,33) and other developing nations, such as Egypt (24) and China (34), have become highly resistant to antimicrobials. DFIs in regions with warmer climates, including India, the Middle East, and Africa, most commonly are caused by P. aeruginosa (35), attributed in part to the warm, humid environment causing foot sweating, self-treatment with antimicrobials, and self-contamination from suboptimal perineal and hand hygiene (36,37).…”
Section: Microbiology Of Dfismentioning
confidence: 99%